IMPROVING FINANCIAL BEHAVIOR OF MILLENNIAL GENERATION THROUGH ATTITUDE, KNOWLEDGE, AND CONFIDENCE DURING THE COVID-19 PANDEMIC - Yudha, Aji; Martanti, Elisa (Universitas Brawijaya, Indonesia, 2022)
The COVID-19 pandemic has increased people's expenses, so good knowledge in managing finances is needed. The millennial generation is one of the community groups known to be consumptive and have a low level of financial literacy. Whether or not financial management is good is based on the level of community financial literacy. That indicates that the better people's financial literacy, the better they will manage finances. Financial literacy consists of financial behavior, financial attitude, financial knowledge, and financial confidence. Therefore, this study examines the relationship between financial attitude, financial knowledge, and financial confidence in financial behavior. This study also establishes a comprehensive financial literacy model to increase financial literacy during the COVID-19 pandemic. Lastly, this study contributes to the literature developing a financial literacy model for millennials in small towns. This study involved 146 respondents from the millennial generation in Rembang City. Testing was carried out using SEM GeSCA. The results indicated that the factors that directly affect financial behavior are financial attitude and financial confidence. Financial knowledge was found to influence financial behavior indirectly. However, the study results revealed that financial knowledge does not directly affect financial behavior. Future studies can add new variables with a larger sample to obtain more general results.